From soil to grape and wine: Variation of light and heavy elements isotope ratios. (1st November 2016) - Durante, Caterina; Bertacchini, Lucia; Bontempo, Luana; Camin, Federica; Manzini, Daniela; Lambertini, Paolo; Marchetti, Andrea; Paolini, Mauro
Highlights: The variation of heavy and light isotopes along the winemaking process of two oenological products was investigated. A correspondence between isotopic values coming from soil and vine-branch samples was assessed. Isotopic ratio of 87 Sr/ 86 Sr do not vary significantly from grape to wine. δ 15 N has been proposed as further isotopic marker for the geographical characterisation of grape products. Abstract: In the development of a geographical traceability model, it is necessary to understand if the value of the monitored indicators in a food is correlated to its origin or if it is also influenced by 'external factors' such as those coming from its production. In this study, a deeper investigation of the trend of direct geographical traceability indicators along the winemaking process of two traditional oenological products was carried out. Different processes were monitored, sampling each step of their production (grape juice, intermediate products and wine). The results related to the determinations of δ 18 O, (D/H)I, (D/H)II, δ 13 C, δ 15 N and 87 Sr/ 86 Sr have been reported. Furthermore, correspondence with the isotopic values coming from the respective soil and vine-branch samples have been investigated as well, showing the optimal traceability power of the monitored geographical tracers.